Anesthetic management of a patient with large atrial septal defect undergoing laparoscopic cholecystectomy: A case report - Yeon Soo Park; Ji Yeon Kim (Saudi Journal of Anaesthesia, 2020)
A 51-year-old woman presented with symptomatic GB stone was planned for elective laparoscopic cholecystectomy. She had known osteum secondum type atrial septal defect, moderate pulmonary hypertension, and atrial fibrillation. We report the case of a patient with a large atrial septal defect (65 mm) and hemodynamic instability who underwent laparoscopic cholecystectomy under total intravenous anesthesia with careful hemodynamic monitoring. Thorough surveillance and effort could help to make the surgery successful.